2019
DOI: 10.1177/1468087419836178
|View full text |Cite
|
Sign up to set email alerts
|

A critical review of flow field analysis methods involving proper orthogonal decomposition and quadruple proper orthogonal decomposition for internal combustion engines

Abstract: Experimental techniques like particle image velocimetry provide a powerful technical support for the analysis of the spatial and temporal evolution of the flow field in internal combustion engines. Such techniques can be used to investigate both ensemble-averaged flow structures and their cyclic variations. These last are among the major causes of cycle-to-cycle variability of the engine processes (mixture formation, combustion, heat transfer, emission formation), the reduction of which has become a paradigm r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…To obtain more information on the degree of CCV, more advanced POD techniques are developed and applied. Qin proposed a further decomposition method, the quadruple POD decomposition, 42 and a review on the application of these methods to an ICE; the original POD quadruple decomposition applied in this work can be found in a previous work by Rulli et al 33 For the sake of clarity, the proposed POD quadruple decomposition is here recalled. According to equation (8), each snapshot can be reconstructed using the whole set ( N ) of POD coefficient and modes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To obtain more information on the degree of CCV, more advanced POD techniques are developed and applied. Qin proposed a further decomposition method, the quadruple POD decomposition, 42 and a review on the application of these methods to an ICE; the original POD quadruple decomposition applied in this work can be found in a previous work by Rulli et al 33 For the sake of clarity, the proposed POD quadruple decomposition is here recalled. According to equation (8), each snapshot can be reconstructed using the whole set ( N ) of POD coefficient and modes.…”
Section: Resultsmentioning
confidence: 99%
“…This technique allows recognition of the dimension of the dominant flow structures in each reconstructed POD mode. Detailed information on the implementation of the method can be found in Rulli et al 33 The transition part of the turbulence is identified as a passage in the energy cascade between the large-scale vortices in the coherent turbulence and the smallest ones in the incoherent background turbulence. The authors deliberately avoid defining a method to objectively identify the cut-off number between the transition and the incoherent parts of the turbulent.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As for commercial gasolines, carbon-atom rich fuels belonging to the aromatic hydrocarbon class [4] are more prone to generate soot, especially in fuel-rich mixture combustion, when the fuel pyrolysis process is triggered. Emissions in ICEs can be investigated with both experiments at the test bench and Computational Fluid Dynamics (CFD): accurate description of flow field [5], spray [6] [7], mixing [8], combustion [9] [10], knock [11] [12], and emission formation [13] can be achieved with advanced models. The estimation of soot production during fuel oxidation via CFD tools can be achieved both employing detailed chemistry resolution [14] and a chemistry-tabulated approach [8] [15].…”
Section: Introductionmentioning
confidence: 99%
“…To tackle this problem, actual fuels are replaced by so-called fuel surrogates, which are mixtures of fewer well-known hydrocarbons; the composition depends on the properties of the reference fuel that are to be matched. Surrogates have been extensively adopted for several applications, from commercial gasolines [16] to jet fuels [5] [6]. Although Toluene Reference Fuel (TRF) and Primary Reference Fuel (PRF) do not match the evaporation properties of the real gasolines, due to the absence of high-temperature normal boiling point components, such surrogates are widely adopted in DISI engine combustion simulations.…”
Section: Introductionmentioning
confidence: 99%